2021
DOI: 10.1001/jamaneurol.2020.3962
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Ambient Air Pollution and Amyloid Positron Emission Tomography Positivity in Older Adults With Cognitive Impairment

Abstract: IMPORTANCE Amyloid-β (Aβ) deposition is a feature of Alzheimer disease (AD) and may be promoted by exogenous factors, such as ambient air quality.OBJECTIVE To examine the association between the likelihood of amyloid positron emission tomography (PET) scan positivity and ambient air quality in individuals with cognitive impairment. DESIGN, SETTING, AND PARTICIPANTSThis cross-sectional study used data from the Imaging Dementia-Evidence for Amyloid Scanning Study, which included more than 18 000 US participants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
51
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(54 citation statements)
references
References 71 publications
(177 reference statements)
3
51
0
Order By: Relevance
“…The recent spate of wildfires around the globe have provoked concern that smoke exposures may promote vascular and, by extension, neurological consequences 35,36 . While clear relationships between ambient air pollutants, such as PM2.5 and carbon monoxide, and increased incidence of ADRD have been reported 7,8,9 , there have been no specific assessments of wildfire smoke PM impacts on neuroinflammation or markers of ADRD. Findings of the present study confirm that the WFS-derived PM2.5 traveling from distant wildfires can promote numerous outcomes consistent with ADRD pathogenesis and neurological aging.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The recent spate of wildfires around the globe have provoked concern that smoke exposures may promote vascular and, by extension, neurological consequences 35,36 . While clear relationships between ambient air pollutants, such as PM2.5 and carbon monoxide, and increased incidence of ADRD have been reported 7,8,9 , there have been no specific assessments of wildfire smoke PM impacts on neuroinflammation or markers of ADRD. Findings of the present study confirm that the WFS-derived PM2.5 traveling from distant wildfires can promote numerous outcomes consistent with ADRD pathogenesis and neurological aging.…”
Section: Discussionmentioning
confidence: 99%
“…Short-and long-term pulmonary, cardiovascular, and neurological outcomes from inhaled ambient PM are well studied; however, relatively little is known about the impact of WFS-derived PM on neurological outcomes -including implications for priming agerelated disease sequelae. Ambient PM2.5 (PM less than 2.5 microns in aerodynamic diameter) has been associated with increased incidence of Alzheimer's disease and related disorders (ADRD), suicide, depression, psychosis, and other adverse neurological outcomes 7,8,9,10 . Impairment of blood brain barrier (BBB) and neuroinflammation has been implicated in pathophysiology of these neurological disorders.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, pollutants can induce many neuro-pathological alterations and affect brain functioning. A recent report indicates that in a cross-sectional study of 18,178 individuals with cognitive impairment, people living in areas with worse air quality were more likely to have positive amyloid positron emission tomography scan results [ 82 ].…”
Section: Herv Dysregulation Ad and Neurological Diseasesmentioning
confidence: 99%
“…Moreover, higher particulate (PM 2.5 ) air levels appeared to be associated with brain amyloid-β plaques, one neuropathological hallmark of AD [ 82 ]. Therefore, exposure to air pollution is associated with amyloid-β pathology in older adults and increases the risk of cognitive impairment and AD.…”
Section: Herv Dysregulation Ad and Neurological Diseasesmentioning
confidence: 99%
“…A cohort study conducted in Ontario, Canada by 22 simultaneously accessed the effects of PM2.5, NO2, and O3 on dementia risks, and they also found significant associations with PM2.5 and NO2, but not O3. Recent 2018 and 2020 Lancet Commission overviews of modifiable environmental agents associated with disease noted a possible association between air pollutants and dementia, but noted the evidence still preliminary 1,23 .The epidemiologic findings are supported by brain imaging and toxicologic studies.Regarding brain imaging, Shaffer et al (2021)24 have found associations between PM2.5 and AD neuropathology upon autopsy, while Laccarino et al (2020)25 found an association between PM2.5 and positive positron emission tomography (PET) scans for amyloid. Younan et al…”
mentioning
confidence: 99%